Milk agrifood chain, a cuban case - Sablón Cossío, Neyfe (2018)
At the moment, weaknesses in food supply at Cuban supply network coexist, therefore, it is a challenge to increase produc- tion and to reduce the logistic gaps that join the primary production with the commercialization companies, in order to provide consumers with fresh and processed food. This study aims to identify the potential improvement opportunities in the agrifood chain of cow’s milk produced in an area of Cuba at local and regional level. In general, the focus on agrifood chain has a positive impact on meeting the food needs of customers, eases the availability of fresh food in the region, and delivers the supply chain diagnostic as a social contribution. It could be concluded that the deficiency identified in the chain is the low development of the product, customer service, and collaborative performance. They have weaknesses that impact on the final consumer satisfaction.